Effect of temperature and passive ultrasonic irrigation of EDTA 17% in smear layer removal - Fitra Nabiila Alfiona; RR Mahayu Dewi Ariani; Nadia Hardini; Gloria Fortuna (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Smear layer removal in root canal treatment is required to aid the diffusion of intracanal medicament and help sealer penetrate into dentinal tubules. The need for irrigants is important to facilitate smear layer removal in the root canal. Various methods have been proposed in some articles, but their application in apical third still challenges many clinicians due to the complexity of the root canal. This study aimed to analyze the effect of temperature and passive ultrasonic irrigation (PUI) activation of EDTA 17% solution in smear layer removal. Twenty-four extracted mandibular premolars were decoronated to standard root length of 14 mm. The preparation of root canals was completed with crown-down technique using ProTaper FHU to file F3 (30/.09). The root canal irrigation was done with NaOCl 5.25% and EDTA 17% solution. The samples were divided into four groups, namely 25 ºC of EDTA 17% solution (group 1), 37 ºC of EDTA 17% solution (group 2), 25 ºC of EDTA 17% solution with PUI activation (group 3), and 37 ºC of EDTA17% solution with PUI activation (group 4). Smear layer removal was observed under scanning electron microscopy (SEM) and scored ordinally from 1-5. Non-parametric Friedman test showed significant results in all the groups (p<0.05). Post hoc Wilcoxon Signed Rank test showed significant results between group 2 and group 3 (p = 0.039), and between group 3 and group 4 (p = 0.038). The combination methods of temperature and PUI activation showed a significant result in smear layer removal.